A national study of the outcome after treatment of critical aortic stenosis in the neonate. (30th September 2020) - Kjellberg Olofsson, Cecilia; Hanseus, Katarina; Johansson Ramgren, Jens; Johansson Synnergren, Mats; Sunnegårdh, Jan
Abstract: Objective: This study describes short-term and long-term outcome after treatment of critical valvular aortic stenosis in neonates in a national cohort, with surgical valvotomy as first choice intervention. Methods: All neonates in Sweden treated for critical aortic stenosis between 1994 and 2016 were included. Patient files were analysed and cross-checked against the Swedish National Population Registry as of December 2017, giving complete survival data. Diagnosis was confirmed by reviewing echo studies. Critical aortic stenosis was defined as valvular stenosis with duct-dependent systemic circulation or depressed left ventricular function. Primary outcome was all-cause mortality and secondary outcomes were reintervention and aortic valve replacement. Results: Sixty-one patients were identified (50 boys, 11 girls). Primary treatment was surgical valvotomy in 52 neonates and balloon valvotomy in 6. Median age at initial treatment was 5 days (0–26), and median follow-up time was 10.8 years (0.14–22.6). There was no 30-day mortality but four late deaths. Freedom from reintervention was 66%, 61%, 54%, 49%, and 46% at 1, 5, 10, 15, and 20 years, respectively. Median time to reintervention was 3.4 months (4 days to 17.3 years). Valve replacement was performed in 23 patients (38%). Conclusions: Surgical valvotomy is a safe and reliable treatment in these critically ill neonates, with no 30-day mortality and long-term survival of 93% in this national study. At 10 years of age, reintervention was performed in 54% and at end of follow-up 38% had had an aortic valve replacement.